2020
DOI: 10.3390/civileng1030013
|View full text |Cite
|
Sign up to set email alerts
|

Fire Rating of Post-Installed Anchors and Rebars

Abstract: Fire safety is a critical performance aspect of construction products, and post-installed anchors and rebars are no exemption in that regard. During their service life, anchors and rebars are subjected to different kinds of load actions, so they have to be qualified and designed for critical safety performance. While the qualification guidelines for static and seismic loading have matured to conclusive requirements over the past two decades, the requirements for determining the resistance to fire are just abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…10 Beyond typical quasi-static loads, research has identified the performance of anchors against concrete cone breakout failure in case of external confinement/prestressing, 11,12 dynamic and seismic actions, [13][14][15][16] and fire. [17][18][19][20] The resistance is also affected, generally adversely, by the existence of cracks and reinforcement in concrete; an indepth explanation of disruption in the stress flow around and anchor due to cracking and reinforcement can be drawn from the studies by Eligehausen et al 21,22 The positive effects of supplementary hanger reinforcement in the load-bearing capacity of anchors against breakout failure, are discussed for cast-in systems considering static loads in the study by Sharma et al 23 and seismic actions in the study by Petersen et al 24 and as a strengthening method with post-installed hanger reinforcement in the study by Vita et al 25 Neupane et al 26 provides a thorough literature review with focus on tensile anchor failure, pronouncing the challenges and uncertainties of finite element modeling of anchors in concrete, particularly observing the sensitivities from the precise anchor geometry and the lack of case studies with respect to interrupted boundaries near the anchor, particularly cracks in concrete. Undercut anchors modeled in an FE environment also including simulated cracks in concrete are presented in the studies by Mellios et al, 27,28 as part of an investigation for a strengthening application, also indicating a good agreement with experimental results.…”
Section: Behavior Of Anchors In Tension Subject To Concrete Cone Failurementioning
confidence: 99%
See 1 more Smart Citation
“…10 Beyond typical quasi-static loads, research has identified the performance of anchors against concrete cone breakout failure in case of external confinement/prestressing, 11,12 dynamic and seismic actions, [13][14][15][16] and fire. [17][18][19][20] The resistance is also affected, generally adversely, by the existence of cracks and reinforcement in concrete; an indepth explanation of disruption in the stress flow around and anchor due to cracking and reinforcement can be drawn from the studies by Eligehausen et al 21,22 The positive effects of supplementary hanger reinforcement in the load-bearing capacity of anchors against breakout failure, are discussed for cast-in systems considering static loads in the study by Sharma et al 23 and seismic actions in the study by Petersen et al 24 and as a strengthening method with post-installed hanger reinforcement in the study by Vita et al 25 Neupane et al 26 provides a thorough literature review with focus on tensile anchor failure, pronouncing the challenges and uncertainties of finite element modeling of anchors in concrete, particularly observing the sensitivities from the precise anchor geometry and the lack of case studies with respect to interrupted boundaries near the anchor, particularly cracks in concrete. Undercut anchors modeled in an FE environment also including simulated cracks in concrete are presented in the studies by Mellios et al, 27,28 as part of an investigation for a strengthening application, also indicating a good agreement with experimental results.…”
Section: Behavior Of Anchors In Tension Subject To Concrete Cone Failurementioning
confidence: 99%
“…Effects of the anchor head size and the concrete member thickness are investigated by Nilforoush et al 4 Specific aspects of non‐standards concrete material properties are presented with respect to aggregate type in the study by Ninčević et al, 5 curing state in the study by Ninčević and colleagues, 6–8 the influence of low‐emission concrete binders in the study by Al‐Yousuf and colleagues, 7,9 and the inclusion of fiber reinforcement in the study by Spyridis and Mellios 10 . Beyond typical quasi‐static loads, research has identified the performance of anchors against concrete cone breakout failure in case of external confinement/prestressing, 11,12 dynamic and seismic actions, 13–16 and fire 17–20 . The resistance is also affected, generally adversely, by the existence of cracks and reinforcement in concrete; an in‐depth explanation of disruption in the stress flow around and anchor due to cracking and reinforcement can be drawn from the studies by Eligehausen et al 21,22 The positive effects of supplementary hanger reinforcement in the load‐bearing capacity of anchors against breakout failure, are discussed for cast‐in systems considering static loads in the study by Sharma et al 23 and seismic actions in the study by Petersen et al 24 and as a strengthening method with post‐installed hanger reinforcement in the study by Vita et al 25 Neupane et al 26 provides a thorough literature review with focus on tensile anchor failure, pronouncing the challenges and uncertainties of finite element modeling of anchors in concrete, particularly observing the sensitivities from the precise anchor geometry and the lack of case studies with respect to interrupted boundaries near the anchor, particularly cracks in concrete.…”
Section: Load Resistance Of Fastenings In Concrete According To the C...mentioning
confidence: 99%
“…This problem often requires important efforts, as highlighted recently in a detailed discussion of the evaluation process to determine the fire resistance of anchor channels [9]. For post-installed anchors and rebars, a recent review presents the status of the regulations, as well as the underlying background [10]. Regarding bonded anchors, since the available bonding materials are mainly sensitive to temperature increases, the pull-out failure tends to be the most probable failure mode under high-temperature conditions.…”
Section: Introductionmentioning
confidence: 99%